Articles of the mejelle on salam contract: juristic evaluation and applications - Habibur Rahman, Muhammad; Amanullah, Muhammad (Academy of Islamic Studies, University of Malaya, 2020)
The Majallat al-Aḥkām al-‘Adliyyah, known as the Mejelle, is the code of Islamic civil transactions which was prepared under the auspices of the Ottoman Caliphate. This code was established based on the Ḥanafī School of Islamic law. However, people, who follow other than the Ḥanafī School, are reluctant to rely on the Mejelle even though they are interested to know the stands of their respective School of Islamic law on the articles of the Mejelle. Thus, considering the importance and relevance of Salam contract to the contemporary context, the paper attempts to conduct a juristic evaluation of the articles of the Mejelle on salam contract along with an investigation of its contemporary applications. Salam is a sale contract in which the commodity’s delivery is deferred until a defined period, while the buyer must settle the payment upon the contract’s conclusion. Although the general principle says that sale of something which is not possessed and not present is not permissible, salam contract is made valid as an exception from this, considering the need of the people. The study follows a qualitative approach and uses the content analysis method toachieve the objectives. For data source and analysis, the study consults with related classical and contemporary literature. The study finds that in general, the articles of the Mejelle on salam contract conform to the prominent Schools of Islamic law. Among the notable contemporary applications of salam contract are salam financing, parallel salam, salam ṣukūk, salam in short selling, and so forth.